EFEKTIFITAS IMPLEMENTASI PEMBELAJARAN DARING (FULL ONLINE) DIMASA PANDEMI COVID- 19 PADA JENJANG SEKOLAH DASAR DI KABUPATEN SUBANG - Roni Hamdani, Acep; Priatna, Asep (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2020)
This research is motivated by the existence of full online learning (full online) as a result of Covid-19, it is rumored that online learning is less effective, because there is no maximum preparation in terms of regulation, field implementation, and also students, as well as various supporting infrastructure for online learning Therefore, researchers have a desire to test the effectiveness of learning, because there should be no learning content lost in the middle of this pandemic. The research method used was a survey method, with the instrument used was a questionnaire, which was distributed to 80 random elementary school teachers in Subang Regency. Based on the results of the study the effectiveness of learning from the 8 indicators studied is around 66.97%.